Reversible Contraceptive Potential of FDA Approved Excipient N, N-Dimethylacetamide in Male Rats - Khera, Nupur; Ghayor, Chafik; Lindholm, Anna K.; Pavlova, Ekaterina; Atanassova, Nina; Weber, Franz E. (Frontiers in Physiology, 2020)
Development of an effective male contraceptive agent remains a challenge. The present study evaluates the potential of N, N-Dimethylacetamide (DMA), a FDA approved excipient as a male contraceptive agent. Male Sprague Dawley rats injected with DMA for a period of 8 weeks (one injection per week) showed a significant alteration of reproductive parameters. Furthermore, DMA treated animals showed complete infertility in a dose dependent manner, as no pups were born despite proper mating between females and DMA treated males. However, stopping the DMA treatment for a period of 8 weeks (after the initial treatment) restored the reproductive parameters to normal. Moreover, the fertility was resumed to normal as pups were born in the groups where DMA treatment was halted after initial DMA treatment. All these changes had no effect on the level of reproductive hormones FSH, LH and testosterone. Taken together, our results indicate that DMA acts in a reversible and non-hormonal manner to achieve contraception in rats. Therefore, repurposing the use of DMA could lead in a short time to an inexpensive and safer male contraceptive option.